A new species of Melzerella Lima from Bolivia (Coleoptera: Cerambycidae: Lamiinae: Aerenicini) with a key to known species - Wappes, James E.; Lingafelter, Steven W. (Zootaxa, 2011)
A new species of Melzerella Lima is described from Santa Cruz Department, Bolivia. A key to the four known species is provided, along with color photographs documenting their vibrant patterns.